Trifunctional antibody-cytokine fusion protein formats for tumor-targeted combination of IL-15 with IL-7 or IL-21 - Möller, Annika M.; Vettermann, Sarah; Baumann, Felix; Pütter, Max; Müller, Dafne (Frontiers in Immunology, 2025)
Cytokines from the common gamma chain receptor family, such as IL-15, IL-21 and IL-7, show promise for cancer immunotherapy and have been incorporated individually into the immunocytokine approach. However, their efficacy as monotherapy is limited. Here, we investigated the molecular design of tumor-directed trifunctional antibody-cytokine fusion proteins for a combinatorial approach of IL-15 with either IL-7 or IL-21. Various fusion proteins differing in antibody format, cytokine composition and arrangement were generated and cooperative cytokine activity assessed in solution and bound to target cells. Comparative analysis revealed that formats with cytokines positioned at the N- and C-termini of the antibody were more effective than those arranged in series. For the former design, cooperative effects were observed with the scFv-based (IL-15+IL-7) trifunctional fusion protein, primarily enhancing the proliferation of naive T cells, while the scFv/Fab-based (IL-15+IL-21) trifunctional fusion proteins enhanced IFN-y release and the cytotoxic potential of T cells. Combining cytokines in the two-in-one molecule approach was principally advantageous when bound to target cells. Greater potency in inducing JAK-STAT pathway activation highlighted the importance of cytokine colocalization for cooperative receptor activation. Compared to the Fab-based (IL-15+IL-21) format, the scFv-based (IL-15+IL-21) format displayed a tendency towards higher activity in targeted and lower activity in untargeted settings, emphasizing the targeted concept. Thus, this study underscores the importance of molecular design in developing trifunctional immunocytokines and identified the scFv-based trifunctional (IL-15+IL-21) fusion protein, with the antibody in the central position, as a particularly promising candidate for further drug development.